Evaluating the Frequency of Improvement in Sciatica Pain Relief Following Lumbar Fenestration during the Initial Two-Day Postoperative Hospital Stay - Raza Man; Khalid Mehmood; Muhammad Saqib; Shahid Nawaz; Shahid Nawaz; Asghar Essa; Muhammad Humayun; Muhammad Shafique, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Sciatica, characterized by radiating pain along the sciatic nerve, has a substantial impact on one's quality of life. Lumbar fenestration and laminectomy are frequently performed surgical procedures designed to relieve nerve compression. Aims: This study assessed the occurrence of pain alleviation after various treatments within the first two days of the patient's hospital stay following surgery. Methods: A total of thirty individuals who had lumbar fenestration and laminectomy were included in the study. Pain levels were evaluated using the Visual Analog Scale (VAS) before the surgery and at various time intervals after the surgery. Individuals diagnosed with Cauda Equina Syndrome were not included. The main result was the alleviation of pain, determined by the notable decrease in VAS scores. Additional outcomes assessed were the occurrence of complications and length of hospital stay. Results: Among the sample of 30 patients, 27 individuals (90%) reported experiencing notable alleviation of pain, whereas 3 individuals (10%) continued to have discomfort. The average preoperative VAS score was 8.0, but this value dramatically fell to 2.6 after the operation (p < 0.001). Patients who did not have any difficulties consistently reported alleviation from pain, however those who suffered issues such as lower limb weakness, missing dorsal tumor or incorrect level surgery, continued to endure prolonged discomfort. The occurrence of complications was strongly linked to the existence of persistent discomfort (p < 0.001). Patients who experienced persistent pain had a substantially longer hospital stay (mean = 6.3 days) compared to those who had pain alleviation (mean = 4.2 days) (p < 0.05). Conclusion: Lumbar fenestration and laminectomy are quite successful in alleviating sciatica pain immediately after surgery. Postoperative complications have a significant impact on the effectiveness of pain treatment, highlighting the need of precise surgery and comprehensive preoperative planning.